Preliminary research: Gas mixture flowrate detector based on acoustic measurement - Melany Febrina; Eko Satria; Mitra Djamal (Newton-Maxwell Journal of Physics, 2021)
In preliminary research, a system for detecting the flow rate of the gas mixture (N2 and CO2) has been successfully built using acoustic measurements. This detector consists of a speaker as a transmitter of ultrasonic waves, and 3 microphones as a receiver of the ultrasonic waves. The quantity measured in this detection system test is the phase difference of the ultrasonic waves captured by the left and right microphones. The flow rate of the gas mixture will affect the phase difference value between the left and right microphones. With the increase of the flow rate of the gas mixture, the phase difference between the two microphones will increase. The flowrate range tested was between 0 and 0.8 l/min, with a concentration of 20% CO2 in the gas mixture of N2 and CO2. In testing this detection system, the absolute error is 2,4 10-2 l/min.